2021
DOI: 10.1111/jbi.14220
|View full text |Cite
|
Sign up to set email alerts
|

The ectomycorrhizal fungal communities react differently to climatic, edaphic and spatial variables depending on their host species

Abstract: Aim: Ectomycorrhizal (ECM) fungal community structures can vary across sites at a regional scale (>1,000 km), affected by abiotic and biotic environments, dispersal abilities of the fungi, or ecological drift, even among forests of the same host tree species.The spatial patterns of such variation may differ among associated host species and their growth environments, but our knowledge about this remains limited. In the present study, we aimed to investigate whether the ECM fungal community structures (i.e. spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…While soil variables had varying degrees of importance, their roles were generally secondary to climate variables, particularly in community composition. The stronger influence of climate factors compared with soil factors on EM fungal communities agrees with the findings of global studies (Větrovský et al, 2019) and local‐scale studies conducted in Japan (Shigyo & Hirao, 2021; Sugiyama et al, 2021). Moreover, in the mountains of central Japan, soil properties have been reported to be more important drivers of the richness patterns of saprotrophic fungi than of EM fungi (Ogwu et al, 2019; Shigyo & Hirao, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…While soil variables had varying degrees of importance, their roles were generally secondary to climate variables, particularly in community composition. The stronger influence of climate factors compared with soil factors on EM fungal communities agrees with the findings of global studies (Větrovský et al, 2019) and local‐scale studies conducted in Japan (Shigyo & Hirao, 2021; Sugiyama et al, 2021). Moreover, in the mountains of central Japan, soil properties have been reported to be more important drivers of the richness patterns of saprotrophic fungi than of EM fungi (Ogwu et al, 2019; Shigyo & Hirao, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…The results showed that overall ectomycorrhizal fungal community structure differed significantly among three different vegetation (Fig. 5), which supported our second hypothesis, confirming previous results which showed that ECM community structures may be directly impacted by their host (Sugiyama et al 2021;Rosinger et al 2018;Scheibe et al 2015;Urbanová et al 2015;Saitta et al 2018;Molina and Horton 2015). Differences in soil microbiome among different samples were mainly caused by the plant community, as observed in other mining site under a revegetation program.…”
Section: Responses Of Soil Ectomycorrhizal Fungal Community Diversity...supporting
confidence: 88%
“…The deterministic process is mainly determined by abiotic factors ( i.e ., climatic conditions and soil factors) and biotic factors (host plant specificity), which represents the influence of environmental choice on the composition of EM fungal community. It has been found that abiotic factors (soil factors, precipitation) are the decisive factors for EM fungal community compositions ( Mühlmann, Bacher & Peintner, 2008 ; Blaalid et al, 2012 ; Davey et al, 2015 ; Mundra et al, 2015 ; Koizumi & Nara, 2020 ; Sugiyama, Matsuoka & Osono, 2021 ). The research on the EM fungi associated with Kobresia capillifolia , Carex parva , Polygonum macrophyllum , and Potentilla fallens distributed in the Daxueshan, Hongshan, and Baima Snow mountains showed that EM fungi have a preference for host plants ( Gao & Yang, 2016 ).…”
Section: Introductionmentioning
confidence: 99%